Adaptive evolution and functional significance of the PPARGC1A gene across diverse animal species - Seyed Mahdi Hosseini; Farman Ullah; Muhammad Zulfiqar Ahmad; Majid Pasandideh; Aixin Liang; Guohua Hua; Liguo Yang (Ecology and Evolution)
Abstract Codon‐based analyses of the PPARGC1A gene across 38 vertebrate species were deployed to elucidate patterns of evolutionary change. Employing maximum likelihood assessments through MEGA, we scrutinized 447 codon positions addressing the entire coding region, excluding positions mired by gaps or missing data. Distinct codons manifested variance in selection pressures, particularly codons 4, 11, 66, and 123, which exhibited positive dN‐dS values suggestive of positive selection. Codon 137 displayed the most pronounced dN‐dS value, signifying intensified selective advantage. Meanwhile, codons 30 and 90 portrayed near‐neutral scores, indicative of purifying selection. Complementary computational methods (IFEL, REL, FUBAR, and SLAC) confirmed positive selection at specific codon sites, with varying degrees of corroboration. The integration of mixed‐effect modeling (MEME) identified episodic diversifying selection, pinpointing codons that underwent selection episodes in certain lineages. Refined codon model selection lent insight into substitution rates, revealing nuanced degrees of evolutionary conservation among different codons. Supporting these genetic insights, the phylogenetic analysis highlighted relationships among the PPARGC1A sequences and domain analysis confirmed conserved features across species, while protein–protein interaction networks suggested a complex web of functional interdependencies. These findings advance our understanding of the PPARGC1A gene's evolutionary trajectory and underscore the gene's potential adaptive significance within diverse vertebrate lineages.